Effectiveness of Symbiotic in Treatment of Chronic Spontaneous Urticaria: RCT - Muhammad Ali Lal Bux, Talha Laique, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: A challenging health issue nowadays is chronic spontaneous urticaria, which affects almost 2% of the normal population, with half of its sufferers failing to respond to standard treatment therapy. Aim: To determine the efficacy and safety of a symbiotic in the treatment of chronic spontaneous urticaria. Method: This was a randomized trial. This experiment at the Lahore General Hospital involved 204 participants with chronic spontaneous urticaria. Participants were randomized into two groups: oral antihistamines plus an oral probiotic sachet (1.5g) twice daily or oral antihistamines alone for eight weeks. The Urticaria Activity Score was used to evaluate efficacy and safety, while the validated Dermatology Life Quality Index assessed quality of life. An independent sample t-test and a Mann-Whitney test were used to compare the age, UAS7, and DLQI score between the two groups. A p-value ≤0.05 was considered significant. Results: Both treatments significantly improved the UAS7 and DLQI scores from baseline; however, the experimental group produced a significantly greater reduction in the UAS7 and DLQI scores compared to the control group. There was no significant difference in the mean baseline score between both groups. A Wilcoxon signed rank test was used to compare the mean DLQI score before and after treatment in both groups. The results revealed that there was a significant reduction in score from the baseline in both groups. Practical Implication: Due to a lack of clinical data regarding the effective treatment of this health issue, we planned the current project. The results of this study helped us assess the efficacy of probiotics as adjuvant therapy in our local population and added to our local literature. Conclusion: It was concluded that the combination of probiotics and antihistamines showed better efficacy than the antihistamine alone, based on the UAS7 and DLQI scores; hence, they can be used as treatment options among patients. Although further research must be done to validate these findings. Keywords: Efficacy, Safety, Probiotics, DLQI scores, Chronic Urticaria.